A Comparative Analysis of Changing Land Use/Land Cover of Jammu and Srinagar Cities (1981- 2011) - Singh, Sanjay; Kour, Tajinder (National Geographical Journal of India, 2022)
The land use/ land cover changes, as the dynamic forces of global environmental change,are central to the sustainable development debate. These changes have an impact on a wide range of environmental and landscape attributes including the quality of water, land and air resources, ecosystem processes and function of settlements and the climate system itself through greenhouse gas inuxes and surface effects. The land use/ land cover pattern of a region is an outcome of natural and socio-economic factors and their utilization by the man in time and space. An attempt has been made in this paper to compare the changing land use/ land cover (LU/LC) of Jammu and Srinagar cities between 1981 and 2011. The study was conducted with a vision to detect the land consumption rate/ urban expansion and the changes that have taken place predominantly in their built-up land, to predict probable changes that might take place in the next thirty years using both Geographic Information System (GIS) and Remote Sensing data.